In situ forming gelatin/graphene oxide hydrogels for facilitated C2C12 myoblast differentiation. Issue 7 (8th August 2016) - Lee, Jong Ho; Lee, Yunki; Shin, Yong Cheol; Kim, Min Jeong; Park, Ji Hoon; Hong, Suck Won; Kim, Bongju; Oh, Jin-Woo; Park, Ki Dong; Han, Dong-Wook
ABSTRACT: Recently, numerous studies have focused on the development of scaffolds for skeletal tissue engineering and regeneration with various structures. Among various structures, in situ forming hydrogels have attracted considerable attention because they can provide 3D microenvironments for cells, and their stiffness and elasticity can be easily controlled by physical or chemical means. Over the last decade, graphene oxide (GO) has been widely explored as a potential candidate for biomaterials because of its excellent physicochemical properties and outstanding biocompatibility. In this study, horseradish peroxide-reactive gelatin polymer (GH) hydrogels incorporated with GO were prepared and their physicochemical and biomechanical properties were characterized by scanning electron microscopy, Raman and Fourier transform-infrared spectroscopy, ther-mogravimetric analysis, and rheological study. The cellular behaviors of the C2C12 myoblasts within the GO-incorporated GH (GH/GO) hydrogels were examined by a cell counting kit-8 assay and immunocytochemistry. GO was uniformly distributed inside the GH hydrogels without affecting their physicochemical and biomechanical properties. GH/GO hydrogels facilitated the myogenic differentiation of C2C12 cells without hindering their proliferation. These results suggest that GH/GO hydrogels can be exploited to craft a range of strategies for the development of promising scaffolds to accelerate skeletal tissue regeneration because of their potential to stimulate myogenesis.